Pencil beam scanning proton therapy for treatment of the retroperitoneum after nephrectomy for Wilms tumor: A dosimetric comparison study. Issue 1 (27th August 2016) - Vogel, Jennifer; Lin, Haibo; Both, Stefan; Tochner, Zelig; Balis, Frank; Hill‐Kayser, Christine
Abstract: Background: Multimodality treatment for patients with Wilms tumor has improved patient survival, but is associated with acute and long‐term toxicity, partially due to irradiation. Proton therapy using pencil beam scanning (PBS) is a promising technique to reduce dose to organs at risk (OAR). In this study, we evaluate PBS plans for postoperative irradiation in patients with Wilms tumor. Procedure: Patients were treated with anterior‐posterior–posterior‐anterior (AP–PA) photon fields encompassing the preoperative tumor volume. Patients requiring whole lung irradiation were treated with AP–PA photon fields covering the bilateral lungs. Prescription doses were generally 1, 080 and 1, 200 cGy, respectively. Flank PBS plans encompassing the ipsilateral retroperitoneum and para‐arotic nodes were generated for dosimetric evaluation. Results: Treatment records and comparison plans of 11 patients were reviewed. Mean dose and median dose to 50% or more of the contralateral kidney (D50) were 135 cGy and 139 cGy with photons and 52 cGy relative biological effectiveness (RBE) ( P = 0.009) and 5 cGy RBE ( P = 0.000001) with PBS. Mean dose and median D50 to bowel was 639 cGy and 979 cGy with photons and 379 cGy RBE ( P = 0.001) and 47 cGy RBE ( P = 0.004) with PBS. Mean dose and median D50 to the liver were 755 cGy and 1, 013 cGy with photons and 411 cGy RBE ( P = 0.02) and 132 cGy RBE ( P = 0.02) with PBS. For patients with right‐sided tumors, mean liver dose following sequential whole lung irradiation was 1, 252 cGy with photons and 845 cGy RBE ( P = 0.04) with PBS. Discussions: PBS proton therapy is a feasible method for irradiating the retroperitoneum and provides significant sparing of dose to critical OAR. This may translate to improved long‐term health outcomes for patients and warrants further clinical investigation.